1997
DOI: 10.1056/nejm199711273372203
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Activated Endothelial Cells in Sickle Cell Anemia

Abstract: Our studies suggest that the vascular endothelium is activated in patients with sickle cell anemia, regardless of the patients' clinical status. Adhesion proteins on activated endothelial cells may have a role in the vascular pathology of sickle cell disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
426
3
16

Year Published

2000
2000
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 589 publications
(474 citation statements)
references
References 25 publications
16
426
3
16
Order By: Relevance
“…Circulating endothelial cells from SCD patients present an abnormal expression of VCAM-1, ICAM-1, and E-selectin [3]. The increases observed in sVCAM-1 and sICAM-1 levels probably reflect an increased level of endothelial cell adhesion molecule expression and activation in patients and an increased capacity for the adhesion of sickle erythrocytes and leukocytes to the endothelium.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Circulating endothelial cells from SCD patients present an abnormal expression of VCAM-1, ICAM-1, and E-selectin [3]. The increases observed in sVCAM-1 and sICAM-1 levels probably reflect an increased level of endothelial cell adhesion molecule expression and activation in patients and an increased capacity for the adhesion of sickle erythrocytes and leukocytes to the endothelium.…”
Section: Discussionmentioning
confidence: 97%
“…The vascular endothelium appears to be abnormally activated in SCD; for example, circulating endothelial cells (CEC) demonstrate increased expression of the adhesion molecules, VCAM-1, ICAM-1, and E-selectin [3]. VCAM-1 binds the integrin, VLA-4, (expressed by sickle erythrocytes), and its expression on endothelial cells may be stimulated by cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…CECs were defined as negative for CD45 and positive for CD34 and P1H12 (9,25). Activated CECs were defined as negative for CD45, positive for P1H12, and positive for CD62 or CD106 (9,25).…”
Section: Methodsmentioning
confidence: 99%
“…In humans, CECs have been detected in diverse conditions having in common endothelial damage, such as coronary angioplasty, acute coronary syndrome, sickle cell anemia, thrombotic thrombocytopenic purpura, infection with Rickettsia conorii or cytomegalovirus, Behçet's disease, systemic lupus erythematosus (SLE), and small-vessel vasculitis (7)(8)(9)(10)(11)(12)(13)(14)(15). Moreover, it has been suggested that in response to severe ischemia or cytokine stimuli, circulating endothelial cell progenitors (CEPs) increase and home into sites of angiogenesis and/or vascular damage, and consequently contribute to neovascularization and/or wound-healing processes (16)(17)(18).…”
Section: Conclusion the Presence Of Cecs In Patientsmentioning
confidence: 99%
“…13 Variations in these signals can affect the EC characteristics and thereby contribute to the unpredictable occurrences of VOC. The resulting endothelial injury, indicated by the presence of activated ECs circulating in the blood of SCA patients, 14 could contribute to additional complications. Here, we evaluate the effects of HU on vascular ECs.…”
Section: Introductionmentioning
confidence: 99%